A hazard-agnostic model for unpacking systemic impacts in urban systems. Issue 3 (3rd July 2022) - Beevers, Lindsay; McClymont, Kerri; Bedinger, Melissa
ABSTRACT: To add to the engineer's toolkit for the twenty-first century challenges, we demonstrate a novel systems model for understanding urban impacts. The model captures interdependencies between different interconnected systems (or sectors, e.g. recreational services or public healthcare) in cities, from the tangible (e.g. resources such as roads) to the more intangible (e.g. outcomes such as the sustainable economy). The model is hazard-agnostic in that it can be modified to capture the impacts of different shocks on tangible parts of the system and how these cascade through to more abstract and high-level city tasks and outcomes. This paper demonstrates three hypothetical scenarios (a flood, drought, and pandemic) and their impacts on a generic UK city. Using the network analysis, impacts can be tracked and interpreted to help prioritise requirements for resilience-building. We propose this new tool be taken up and tested by others working to address global challenges such as the Sustainable Development Goals and grappling with the interconnectedness of urban systems.